Context-dependent expression of a conditionally-inducible form of active Akt - Park, Soyeon; Burke, Robert E.; Kareva, Tatyana; Kholodilov, Nikolai; Aimé, Pascaline; Franke, Thomas F.; Levy, Oren; Greene, Lloyd A. (PloS one, 2018)
Akt kinases are key signaling components in proliferation-competent and post-mitotic cells. Here, we sought to create a conditionally-inducible form of active Akt for both in vitro and in vivo applications. We fused a ligand-responsive Destabilizing Domain (DD) derived from E. coli dihydrofolate reductase to a constitutively active mutant form of Akt1, Akt(E40K). Prior work indicated that such fusion proteins may be stabilized and induced by a ligand, the antibiotic Trimethoprim (TMP). We observed dose-dependent, reversible induction of both total and phosphorylated/active DD-Akt(E40K) by TMP across several cellular backgrounds in culture, including neurons. Phosphorylation of FoxO4, an Akt substrate, was significantly elevated after DD-Akt(E40K) induction, indicating the induced protein was functionally active. The induced Akt(E40K) protected cells from apoptosis evoked by serum deprivation and was neuroprotective in two cellular models of Parkinson's disease (6-OHDA and MPP+ exposure). There was no significant protection without induction. We also evaluated Akt(E40K) induction by TMP in mouse substantia nigra and striatum after neuronal delivery via an AAV1 adeno-associated viral vector. While there was significant induction in striatum, there was no apparent induction in substantia nigra. To explore the possible basis for this difference, we examined DD-Akt(E40K) induction in cultured ventral midbrain neurons. Both dopaminergic and non-dopaminergic neurons in the cultures showed DD-Akt(E40K) induction after TMP treatment. However, basal DD-Akt(E40K) expression was 3-fold higher for dopaminergic neurons, resulting in a significantly lower induction by TMP in this population. Such findings suggest that dopaminergic neurons may be relatively inefficient in protein degradation, a property that could relate to their lack of apparent DD-Akt(E40K) induction in vivo and to their selective vulnerability in Parkinson's disease. In summary, we generated an inducible, biologically active form of Akt. The degree of inducibility appears to reflect cellular context that will inform the most appropriate applications for this and related reagents.